Criminal Liability of Directors of Limited Liability Companies Sentenced to Bankruptcy for Bankruptcy Boedel Embezzlement - Setyo Nugroho Haribowo; Hermawan (Universitas Muhammadiyah Palu, 2023)
Limited Liability Company is a legal entity. With its status as a legal entity, it means that the company is a legal subject capable of supporting its rights and obligations as with a person and has its own assets separate from the assets of its founders, shareholders and administrators, since the court pronounces the bankruptcy decision in an open session. For the general public, the debtor has the result that he loses the right to manage and control his assets (persona standy in ludicio) and the bankrupt's rights and obligations are transferred to the curator to manage and control his assets in accordance with the Bankruptcy Law. In principle, directors are fully responsible for running the company and directors are personally responsible if they violate the authority determined by law or the articles of association. ultra virres is when the action taken is beyond the company's capacity as stated in the company's aims and objectives as stated in the Articles of Association. The principle of fiduciary duty applies to company directors in carrying out their duties both in carrying out their functions as management, namely in leading the company and as representation, namely representing the company inside and outside the court. Directors are fully responsible for running the company and directors are personally responsible if they violate the authority determined by law or the Articles of Association. In the event that a Limited Liability Company is sentenced to bankruptcy, the Directors of the Limited Liability Company may not transfer its bankruptcy certificate, if this happens, the Directors of the Limited Liability Company may be subject to the crime of embezzlement.